ECONOMIC IMPACT OF THE JAKARTA–BANDUNG HIGH-SPEED RAIL ON MALANGNENGAH VILLAGE COMMUNITY - Nisa Mutmainah, Gaida; Mulyawan Thoriq, Arief (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study explores the economic transformation of Malangnengah Village, Sukatani District, Purwakarta Regency, caused by the Jakarta–Bandung High-Speed Rail project. The research aims to describe the changes experienced by the community, analyze their impacts, and evaluate them within the framework of Islamic economics. A qualitative descriptive method was applied, with data collected through observation, in-depth interviews, and documentation. The findings reveal significant disruptions in local livelihoods, including the decline of agriculture, the cessation of PT Hanusentra Agroselo’s operations, and the weakening of the village cooperative (KUD). Household incomes decreased, purchasing power fell, and many residents shifted to informal or precarious jobs. Public facilities such as schools and sports fields were relocated, affecting social cohesion. Several families became dependent on external assistance, reducing their economic resilience. From an Islamic economic perspective, these conditions show the lack of distributive justice (al-‘adl), protection of wealth (hifdz al-mal), and public welfare (maslahah). The study concludes that infrastructure development should not only pursue growth but also ensure fairness, protection, and sustainability for local communities.